Workbook for Practical Microbiology - Bhumbla, U. Upasana (Jaypee Brothers Medical Publishers, 2018)
The intent of this book, Workbook for Practical Microbiology, is to provide a workbook to the practical exercises in microbiology, which covers all the important topics such as history of microbiology, microscopy, sterilization and disinfection, laboratory instruments, simple staining, gram's staining, morphology of bacteria, hanging drop examination, albert's staining, culture media and methods, principles and uses of antimicrobial agents, serology, stool examination, morphology of fungi, and hand hygiene. This book has been designed in a pattern to help students, learn and work on the practical aspects of microbiology. This book is written in a workbook style, so that students are able to understand and write the practical notes.